PROGRAM KEMITRAAN MASYARAKAT BAGI KELOMPOK KADER TENGGUH MASA NEW NORMAL DALAM PEMANTAUAN IBU HAMIL DENGAN PEMANFAATAN BUKU KIA DI WILAYAH PUSKESMAS MULYOREJO KOTA MALANG - Suprapti; Triningsih, Reni Wahyu; Setyarini, Didien Ika (DHARMA BAKTI, 2021)
One of the main investments in health development in Indonesia is human resources.In its implementation, it is manifested in the form of disease prevention (preventive)activities, health promotion (promotive), disease treatment (curative), and health recovery(rehabilitative). However, early 2020 there was a pandemic of COVID-19 infection that canaffect anyone. With this condition, it is possible to have an effect on the high maternalmortality rate (MMR). Therefore, this condition requires physical, physical readiness,especially for pregnant women and children who are categorized as susceptible to infectionand require close supervision 'in the COVID-19 pandemic situation, on the other hand thereis a limitation of almost all routine services including health services. maternal and neonatal.The situation above, can cause pregnant women to be reluctant to go to puskesmas or otherhealth service facilities for fear of contracting, the arrangement of pregnancy examinationsand classes of pregnant women with health protocols, as well as the unpreparedness ofservices in terms of personnel and infrastructure including Personal Protective Equipment.This service activity is carried out by means of online training with this community servicepartner is Puskesmas Mulyorejo Malang City, where the target target of this training activityis health cadres. The purpose of this activity is to carry out a partnership program with thetarget of monitoring pregnant women using the MCH handbook. The results of thiscommunity service activity were the formation of tough cadres during the pandemic andincreased knowledge of health cadres' skills in monitoring pregnant women using the KIAbook during the Cofid-19 pandemic